How to give your users the LIS services they want - Pantry, Sheila; Griffiths, Peter 1948- (Facet, 2009)
This title will help any library or information professional anywhere to take a fresh look at this area and to tackle it in their organization, so as to ensure that their users will always obtain exactly what they want.
Includes bibliographical references and index
Keywords: Libraries / User satisfaction; Information services / User education; Library administration; Information services -- User education; Libraries -- User satisfaction; Public services (Libraries); Benutzer; Bibliothek; Dienstleistung